2019
DOI: 10.1051/0004-6361/201833870
|View full text |Cite
|
Sign up to set email alerts
|

Herschel-HOBYS study of the earliest phases of high-mass star formation in NGC 6357

Abstract: Aims. To constrain models of high-mass star formation it is important to identify the massive dense cores (MDCs) that are able to form high-mass star(s). This is one of the purposes of the Herschel/HOBYS key programme. Here, we carry out the census and characterise of the properties of the MDCs population of the NGC 6357 H II region. Methods. Our study is based on the Herschel/PACS and SPIRE 70−500 μm images of NGC 6357 complemented with (sub-)millimetre and mid-infrared data. We followed the procedure establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 110 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…The reference band is 160 µm or, if there is no reliable 160 µm detection, the 250 µm band. Following Tigé et al (2017) and Russeil et al (2019), a number of criteria are applied to the getsources extraction to select the most reliable detections. In each band, a reliable detection requires that the signal-to-noise ratio is above 2 for both the peak and integrated fluxes and that the monochromatic significance (reported by getsources) is above 5.…”
Section: Summary Of Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference band is 160 µm or, if there is no reliable 160 µm detection, the 250 µm band. Following Tigé et al (2017) and Russeil et al (2019), a number of criteria are applied to the getsources extraction to select the most reliable detections. In each band, a reliable detection requires that the signal-to-noise ratio is above 2 for both the peak and integrated fluxes and that the monochromatic significance (reported by getsources) is above 5.…”
Section: Summary Of Results and Conclusionmentioning
confidence: 99%
“…The maximum size of prestellar cores extracted from sub-millimeter surveys is ∼ 0.1 pc (Motte et al 1998(Motte et al , 2001Johnstone et al 2006;Könyves et al 2015;Tigé et al 2017;Rayner et al 2017;Bresnahan et al 2018;Russeil et al 2019). In some studies, a maximum core size is imposed as one of the selection criteria to avoid including clumps in the core sample, for example a maximum size of 0.3 pc is adopted in Tigé et al 2017and Russeil et al (2019). The turbulent-core model by Mc-Kee & Tan (2003) predicts a similar core size of ∼ 0.1 pc for progenitors of massive stars and characteristic column densities of star-forming regions (see their equation 20).…”
Section: Prestellar Core Definitionmentioning
confidence: 99%
“…NGC 6357 and NGC 6334 seem to originate from a long, ∼100 pc, filament parallel to the Galactic plane (e.g., Russeil et al 2019). This situation is not unique as in, for example, Serpens, where distinct sites of star formation are noted across a region of 100 pc in length (Herczeg et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, YSOs are mainly associated to clusters Pismis 24 or AH03J1725-34.4 and the YSOs in these clusters as well as the ones in the uniformly distributed stellar population have similar ages (between 1.0 and 1.5 Myr), suggesting that the recent star formation proceeded nearly simultaneously across NGC 6357. From the high-mass protostellar cores study, Russeil et al (2019) suggested that the massive star formation has then stopped for at least the last Myr and that NGC 6357 will not form massive stars anymore. The starformation stoppping can also be seen because only 4% of the mass is in the form of filaments and 9% of the filament mass is in the form of MDCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation